Ogo: A Cultural System Moves and Damage of the Environment - Zainur Wula; Hadjrah Arifin (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
Humans and the natural environment have a very close relationship; it can even be called interdependence. Humans have a very high dependence on fulfilling the necessities of life, the most important of which are clothing, food, and shelter which have the main source of raw materials from the natural environment, especially in communities whose farmers depend on the natural environment and land. The culture of people's lives in the shifting cultivation system called ogo is one of the main factors in forest and environmental damage in a broad sense because forests are not only related to grass and timber trees but also land, rocks, water, fauna. The research method used is qualitative with a case study approach. The data were collected through documents, in-depth interviews, and observations, and data analysis was carried out descriptively. The results showed that forest and environmental damage due to excessive use with the ogo culture of shifting cultivation with a period of three to four years resulted in reduced water reserves due to damage to water infiltration, floods, and landslides as well as damage to residential areas. Roads and bridges in the village of Nuanaga in February 2016. Ogo as a socio-cultural system of shifting cultivation is an act of rational choice by farmers in increasing income and the dignity of family life, despite frequent floods and landslides in the rainy season with high intensity.